An uncommon presentation of hydatid cysts: Renal hydatid disease in two children [Nadir bir hidatik kist tutulumu: İki çocuk hastada renal hidatik kist] - KEPENEKLİ KADAYİFCİ, EDA; ALPAY, HARİKA; GÖKCE, İBRAHİM; YILDIZ, NURDAN; TARCAN, TUFAN (Aves Yayincilik, 2014)
Echinococcus granulosus is the most widespread, serious human cestode infection in the world. It is especially endemic in developing countries. It may involve many organs but the most involved organs are the liver and the lungs. Renal involvement is rare, comprising only 2% to 4% of cases. Renal cyst may be isolated or with cysts in other organs. In this report, we present two cases, the first with isolated renal hydatid cyst and the second with multiple renal cysts and a hepatic cyst. We aimed to draw attention to hydatid cyst disease in the differential diagnosis of renal cysts in children. © 2014 by Pediatric Infectious Diseases Society.
Keywords: Abdominal pain; Differential diagnosis; Hydatid cyst; Kidney involvement